2021
DOI: 10.1038/s41598-021-92530-3
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 upregulation is associated with activation of the DNA double-strand break repair pathway in patients with colitic cancer

Abstract: Ulcerative colitis (UC) is a DNA damage-associated chronic inflammatory disease; the DNA double-strand break (DSB) repair pathway participates in UC-associated dysplasia/colitic cancer carcinogenesis. The DSB/interferon regulatory factor-1 (IRF-1) pathway can induce PD-L1 expression transcriptionally. However, the association of PD-L1/DSB/IRF-1 with sporadic colorectal cancer (SCRC), and UC-associated dysplasia/colitic cancer, remains elusive. Therefore, we investigated the significance of the PD-L1/DSB repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We have shown that PD-1, PD-L1 and A2aR signalling confers OAC cells with a survival advantage as their blockade alone reduces OAC cell viability and can enhance FLOT chemotherapy toxicity. Of relevance, studies have implicated a role for PD-L1 intrinsic signalling in mediating DNA repair in colon cancer 40 . Therefore, to achieve a greater understanding of the mechanisms of action behind enhanced FLOT cytotoxicity in combination with ICB we assessed if blockade of these IC pathways might alter the formation of γH2AX alone and in combination with FLOT chemotherapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that PD-1, PD-L1 and A2aR signalling confers OAC cells with a survival advantage as their blockade alone reduces OAC cell viability and can enhance FLOT chemotherapy toxicity. Of relevance, studies have implicated a role for PD-L1 intrinsic signalling in mediating DNA repair in colon cancer 40 . Therefore, to achieve a greater understanding of the mechanisms of action behind enhanced FLOT cytotoxicity in combination with ICB we assessed if blockade of these IC pathways might alter the formation of γH2AX alone and in combination with FLOT chemotherapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PD-L1 upregulation is associated with activation of the DNA double-strand break repair pathway in patients with colon cancer 40 . Furthermore, several studies have shown that accumulation of damaged DNA and subsequent DNA damage signalling mediates upregulation of PD-L1 on the surface of tumour cells 18 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The PD-1 and PD-L1 may not be associated with disease progression in patients with TNBC, but the level rate of PD-1 and PD-L1 in TNBC tissues was significantly higher than that in non-TNBC, which suggested that PD-1 and PD-L1 had potential involvement in the development of TNBC [7] . PD-L1 disease is expressed in various solid malignancies, including melanoma and lung, bladder, colon, pancreatic as well as head and neck cancers [8,9,10,11] . PD-1 also acts to suppress lymphocytes, thereby limiting autoimmunity by inhibiting PD-L1 [12] .…”
Section: Pd-1 Expression and Therapy In Tnbcmentioning
confidence: 99%
“…In humans, it was shown that patients with UC-associated dysplasia and cancer had increased expression of the PD-1 ligand PD-L1 on CD8 + T cells, as compared to sporadic CRC. PD-L1 overexpression correlated to chronic inflammation-induced DNA damage, and PD-L1 upregulation was mediated by inflammation-induced upregulation of IRF-1 [ 198 ] ( Table 1 ). Whether this exhaustion phenotype on T cells also leads to decreased effector functions of T cells, and thus interferes with their immunosurveillance function, needs further investigation.…”
Section: The Role Of the Immune System In Ibd-associated Cancermentioning
confidence: 99%